RESEARCH ON THE FITTING CLEARANCE BETWEEN FLANGE BORE AND SHAFT CONSIDERING MULTI-ERRORS COUPLING - NI WeiHua; JIANG XiaoHui (Jixie qiangdu, 2018)
The mating state between a flange bore and a shaft and the position error for a flange shaft in a bore has an important influence on the assembly accuracy of precision products.In view of the fact that three-dimensional cylindricity was usually ignored in existing researches,a contact method was developed,which was based on equal vector judgment criterion and measured profile data of the parts.It can effectively determine the actual fitting clearance between bore and shaft taking threedimensional cylindricity errors into account.The effects of the cylindricity error and the number of lobes on the fitting clearance were analyzed in detail.The results indicate that the cylindricity error has significant influence on the actual fitting clearance.By the principal of error composition and neutralization,the actual fitting clearance between a flange bore and shaft was obtained considering the coupling of dimension errors,three-dimensional cylindricity errors and perpendicular errors.It is effective to preanalyze the position accuracy for a flange shaft in a flange bore.Then it can provide guidance for subsequent assembly processes to increase assembly efficiency and improve assembly accuracy of precision products before they are assembled.